2008
DOI: 10.1111/j.1365-2559.2008.03154.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of GCIP in breast carcinoma: relationship with tumour grade, disease‐free survival, mucinous differentiation and response to chemotherapy

Abstract: The current data provide evidence that decreased expression of GCIP in vivo is present in human breast carcinoma and indicate that GCIP is a potential indicator of good prognosis. In patients receiving neoadjuvant chemotherapy, it may also have predictive value for the chemotherapeutic response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…Numerous studies have demonstrated that GCIP functions as a tumor suppressor and is down-regulated in various cancers, [6][7][8][9][10][11][12][13] suggesting that repression of GCIP could promote tumor progression. However, the molecular mechanism responsible for down-regulating GCIP expression in cancer and the function(s) through which GCIP suppresses tumor progression were previously unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that GCIP functions as a tumor suppressor and is down-regulated in various cancers, [6][7][8][9][10][11][12][13] suggesting that repression of GCIP could promote tumor progression. However, the molecular mechanism responsible for down-regulating GCIP expression in cancer and the function(s) through which GCIP suppresses tumor progression were previously unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence indicates that the GCIP is a novel tumor suppressor in breast, colon and liver cancers [22, 27-29]. However, the precise mechanisms underlying its anti-tumor properties have not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Unstained slides were deparaffinized in xylene and rehydrated sequentially in ethanol. Immunohistochemistry analysis of GCIP was performed as previously described[29] and Id1 was described in the Supplementary Data.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations